ANALISIS KELAYAKAN FINANSIAL PRODUK KOPI HERBAL INSTAN TERPRODUKSI OLEH UD. SARI ALAM - Hilda Rosmalia Saida; Nurhayati Nurhayati; Bambang Herry Purnomo; Eka Ruriani (Faculty of Agricultural Technology, University of Jember, 2014)
This study aimed to determine the financial feasibility of the herbal instans coffee produced by UD. Sari Alam. The study used a descriptive and analytical approach. The methods of data analysis include analysis of financial feasibility and sensitivity. This research was, analyzed the sensitivity testing, financial, and scenario financial feasibility. Financial feasibility analysis method used NPV, IRR, BC ratio, PBP, BEP, test sensitivity, financial feasibility and scenarios.The results showed that undertaking the production of herbal instant coffee was declared eligible to run but is very sensitive to changes in the value of the variable that increases in operational costs and a decrease in selling price. The second scenario (production time does is over four times a week) that at least can be taken to reduce the sensitivity of the effort as a result of changes in the value of the variable.Keywords: herbal instan coffee, financial feasibility, pegagan, kayu manis, UD. Sari Alam